Return of State Money in Court Decisions Against Criminal Acts of Corruption - Sartono Gurning; Amshori Amshori (LEGAL BRIEF, 2022)
One of the fundamental issues that is very important and becomes a deeper concern in eradicating corruption is how to recover lost state losses as a result of acts of corruption, whether carried out by individuals or corporations. The phenomenon that has occurred so far is that the eradication of corruption that is carried out can only save 10-15 percent of the total money being corrupted